DYNAMICS BETWEEN SPRING AND FALL HARVESTS OF WILD TURKEYS IN VIRGINIA - David E. Steffen; Gary W. Norman (Wildlife Society Bulletin)
Abstract: Different wild turkey (Meleagris gallopavo silvestris) population growth and density indices have been observed among counties in Virginia. This study was conducted to determine if a relationship existed between different levels of fall harvest and trends in spring harvest. Data collected from mandatory hunter check stations were used to evaluate the relationships between fall and spring harvests from 1983‐84 to 1992‐93. Statewide harvests during this 10‐year period averaged 12,022 birds in fall and 6,987 gobblers in spring. The average composition of fall harvests consisted of 21.7% adult males, 18.0% adult females, and 60.3% juveniles. Four different fall either‐sex hunting seasons (no fall hunting, 2 weeks, 8 weeks, and 9 weeks) among 98 counties allowed the investigation of mean fall harvest levels ranging from 0.0 to 0.463 birds/km2 of forest. The annual rate of increase of statewide spring gobbler harvests was 7.1% (r2 = 0.92, P < 0.01). Spring gobbler harvest trends in all counties were either stable (n = 42) or significantly increasing (n = 56). A significant nonlinear relationship existed between fall harvest levels and the trend in spring gobbler harvests (r2 = 0.30, P < 0.01). Fall harvest levels < 0.1 birds/km2 of forest resulted in greater (P < 0.05) annual spring harvest growth rates (10.4%) than growth rates (6.2%) observed at higher levels of fall harvest. Counties with lower initial spring harvests also experienced higher rates of spring harvest growth during the 10‐year period (P < 0.01). Predicted annual spring harvest growth rates remained low (about 6%) and stable at all fall harvests exceeding 0.1 birds/km2 of forest. Although fall harvest levels and growth rates of spring gobbler harvest were inversely related, annual fall harvest totals and size of the subsequent spring gobbler harvest were not related. Regardless of spring harvest size at the beginning of the 10‐year period, growth rates in spring harvest were positively correlated with growth rates in fall harvests (P < 0.05). Harvest data from West Virginia supported the fall and spring harvest relationships observed in Virginia. If spring gobbler harvest is an index of turkey population size, these results also suggest population trends, population impacts due to fall hunting, density dependence possibilities, potential rates of population increase, and fall harvest management guidelines. Although these results may imply cause‐and‐effect relationships between fall harvest rates and spring gobbler harvest trends, corroborative research investigating the survival and population impacts of fall hunting is needed to confirm these associations.